2012
DOI: 10.1093/eurjhf/hfs060
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate achieved or beta‐blocker dose in patients with chronic heart failure: which is the better target?

Abstract: AimsTo investigate whether the mortality of patients with chronic heart failure (CHF) due to left ventricular systolic dysfunction (LVSD) is more strongly related to beta-blocker dose or to heart rate. It is known that beta-blockers reduce mortality in patients with CHF and LVSD, but the primary mechanism of action is uncertain. Methods and resultsPatients with an ejection fraction ≤40%, who were in sinus rhythm both at an initial (visit 1) and at a 4-month clinic review (visit 2), were followed for a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 43 publications
(42 reference statements)
5
37
1
2
Order By: Relevance
“…Second, and even more remarkable, we observed that lower heart rates are associated with better prognoses in younger patients (<75 years), whereas a U-shaped mortality risk curve was observed in older patients, with a nadir at 68 beats/min. Our results are consistent with the increasingly strong evidence of a relationship between resting heart rate and global outcomes among patients with HF and depressed LVEF in SR, [13][14][15] suggesting that patients with higher heart rates have poorer prognoses. Moreover, a recently published I-Preserve substudy 16 found that heart rate control is also important in patients in SR with preserved ejection fraction, similar to our findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Second, and even more remarkable, we observed that lower heart rates are associated with better prognoses in younger patients (<75 years), whereas a U-shaped mortality risk curve was observed in older patients, with a nadir at 68 beats/min. Our results are consistent with the increasingly strong evidence of a relationship between resting heart rate and global outcomes among patients with HF and depressed LVEF in SR, [13][14][15] suggesting that patients with higher heart rates have poorer prognoses. Moreover, a recently published I-Preserve substudy 16 found that heart rate control is also important in patients in SR with preserved ejection fraction, similar to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Data derived from the SHIFT (Systolic Heart Failure Treatment With the I(f) Inhibitor Ivabradine Trial) study 2 (mean patient age, 60 years) suggest a target cardiac heart rate of less than 60 beats/min but do not define an optimal heart rate range. In an older cohort of patients with a median age of 70 years (interquartile range, 63-76 years), Cullington et al 15 advised not decreasing the heart rate below 50 beats/min and found lower mortality at heart rates (achieved in the second visit to their clinic at 4 months) between 58 and 64 beats/min; their results indicated worse outcomes with heart rates of less than 58 beats/ min. This observation in a cohort of patients with 25% of the population older than 76 years seems to agree with our results.…”
Section: Discussionmentioning
confidence: 99%
“…62 Thus, it may be hypothesised that achieving a HR within the target range may be a more appropriate therapeutic goal than optimising beta-blocker dose in patients with CHF. In SHIFT, patients with the lowest risk reached a HR <60 bpm; therefore it might be reasonable, at present, to recommend this target in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients with chronic HF, heart rate at a 4-month followup clinic visit, but not the initial clinic visit, indicated prognosis independent of β-blocker use or dose, with patients having a heart rate of 58 to 64 beat/min having the best prognosis. 18 Most studies have evaluated heart rate at a single time point, but the interplay between heart rate and outcomes is likely more complex, particularly in the acute setting.…”
Section: Discussionmentioning
confidence: 99%